Standard Precautions for COVID-19: An Insight into the Awareness of Post Graduate Trainee Doctors Working At a Tertiary Level Dedicated COVID Hospital - Rupa Sharma; Gopal Lal Bunkar; Peeyush Damor; Anuja Vashistha; Pratap Bhan Kaushik (Medsci Publications, 2020)
Background: The rapid and extensive spread of the COVID-19 pandemic is a major concern for healthcare profession. Standard Precautions (SP) are the key to contain the spread. Adherence to existing SP is mostly user dependent and it is affected by their awareness. The Post Graduate (PG) trainee doctors are the immediate caregivers in a Dedicated COVID Hospital. The objective was to assess their awareness of SP , identify gaps in knowledge to help in future capacity building. Methodology: The cross sectional study was conducted in June 2020 at RNT Medical College, Udaipur, Rajasthan on 115 PG trainees from all streams. The questionnaire was adapted from standard COVID-19 Outbreak Guidelines from MoHFW , India and Centre for Disease Prevention and Control (CDC) Descriptive statistics were performed based on the percentage of correct answers. Results: Majority (54.8%) had only average awareness of SP . 62.6% displayed correct awareness of hand hygiene while it was much less for respiratory hygiene (12.2%),PPE donning16(13.9%)and doffing16(13.9%) and other elements of SP. Conclusions: Average and lesser awareness of SP elements among PG trainees is a matter of great concern, This indicates the need for frequent on going trainings on SP to be incorporated in the curriculum of the PG training program.